Sequence specific interaction of Mycobacterium smegmatis topoisomerase I with duplex DNA. - Bhaduri, T (1998)
We have identified strong topoisomerase sites (STS) for Mycobacteruim smegmatis topoisomerase I in double-stranded DNA context using electrophoretic mobility shift assay of enzyme-DNA covalent complexes. Mg2+, an essential component for DNA relaxation activity of the enzyme, is not required for binding to DNA. The enzyme makes single-stranded nicks, with transient covalent interaction at the 5'-end of the broken DNA strand, a characteristic akin to prokaryotic topoisomerases. More importantly, the enzyme binds to duplex DNA having a preferred site with high affinity, a property similar to the eukaryotic type I topoisomerases. The preferred cleavage site is mapped on a 65 bp duplex DNA and found to be CG/TCTT. Thus, the enzyme resembles other prokaryotic type I topoisomerases in mechanistics of the reaction, but is similar to eukaryotic enzymes in DNA recognition properties.